Pengaruh Budaya Organisasi, Kepuasan Kerja dan Motivasi Kerja terhadap Gaya Kepemimpinan dan Kinerja Organisasi (Studi pada Lembaga Perkreditan Desa (LPD) di Bali) - Gunawan, Ketut (Jurnal Aplikasi Manajemen, 2009)
This research aims at studying Organizational culture, Working satisfaction and Working Motivation, and their consequences to Leadership style and the Organizational performance at Village Credit Institution in Bali. In this research, Individual unit analysis is to correlated with organization analysis that is the heads of Village Credit Institutions in Bali. Using Slovin postulation, the respondents in this research are 110 out of 1347 Village Credit Institution in Bali which are : Buleleng regency, Jembrana regency, Tabanan regency, Gianyar regency, Klungkung regency, Karangasem regency, Bangli regency, Badung regency, and Denpasar City. The data collection was conducted by interview using questionnaire model and observation technique. To test model of constructed relationship pattern, the researcher used analysis tools that capable of explaining the relationship simultaneously namely Structural Equation Modeling (SEM) by using the program of Analysis of Moment Structure (AMOST) version 5.0. The finding of this research show that : first, Leadership style has positive and significant influence on organizational performance; second, Organizational Culture has positive and significant influence on organizational performance; third, Working Satisfaction has positive and significant influence on organizational performance; fourth, Working Motivation has positive and significant influence on Organizational performance; fifth, Working Motivation has positive and significant influence on Leadership style; sixth, Organizational Culture has positive and significant influence on Leadership Style; seventh, Organizational Culture has positive and significant influence on Working satisfaction; eighth, Working Motivation has positive and significant influence on Working Satisfaction. The new facts found by this research are : Local Culture as a Organizational culture has positive and significant influence on Organizational performance, Working satisfaction and Leadership style.